The Effect of Education Models on Changed Misconceptions About Long-Term Medication Inducing Renal Impairment - Vitarani Dwi Ananda Ningrum; Rahma Yuantari; Irwan Nuryana Kurniawan; Devi Wahyuni (Sanata Dharma University, 2023)
Medication misconceptions become a factor for nonadherence. Education for Posbindu cadres is required as a community empowerment to reduce predispositions to chronic kidney disease caused by medication nonadherence. This quasi-experimental research involved one group pretest-posttest design aiming to compare four education models for Posbindu cadres in PHCs in Yogyakarta with changes in misconceptions about antihypertensives and antidiabetics in long-term use-induced renal impairment. All models employed the cadre smart module with models 3 and 4 involving health-worker collaboration. The added educational media were posters (model 1), leaflets (model 2), and posters-leaflets (model 4). Misconception changes were assessed using a validated questionnaire. Eighty-six female cadres aged 43.7±8.6 years were involved with the majority being at least high-school graduates without hypertension and diabetes mellitus risk factors. Model 3 significantly affected all knowledge domains with discussion and clarification of understanding becoming the strength of the techniques used therein. The results proved the importance of health-worker collaboration in health promotion to increase public knowledge of health and drug use, but varied education media could give no guarantee of improvements in such misconceptions. Interactive techniques through knowledge construction assisted by health-workers, especially for unfamiliar domains among society, are recommended to improve the effectiveness of similar education.